Agathoxylon Hartig in the Lower Cretaceous Arroyo del Pajarito Member (Los Adobes Formation), Chubut Province, Argentina - Vera, Ezequiel Ignacio; Perez Loinaze, Valeria Susana; Llorens, Magdalena; Passalia, Mauro Gabriel (Journal of South American Earth Sciences)
The Cretaceous continental deposits of the Chubut Group are preserved in the Cañadón Asfalto and Golfo de San Jorge basins in Patagonia, Argentina. This unit is known worldwide by the diverse array of tetrapod fauna, including non-avian dinosaurs and other diapsids. Plantremains are somewhat less well known from this unit, in particular in the Cañadón Asfalto Basin region, and only recently several works provided information about foliar impressions and fossil woods. In this contribution, a new report of the ubiquitous genus Agathoxylon is presented from the Arroyo del Pajarito Member of the Los Adobes Formation, representing the second macrofossils described for this formation. Anatomical features allow placing it in Agathoxylon antarcticus (Poole et Cantrill) Pujana, Santillana et Marenssi, 2014, a species found in Mesozoic to Paleogene assemblages from Patagonia and Antarctica. A discussion about the age of the Los Adobes Formation is provided, based on the apparent discordances between palynological and isotopic data. Fil: Vera, Ezequiel Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Perez Loinaze, Valeria Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Llorens, Magdalena. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco". Facultad de Ciencias Naturales - Sede Trelew; Argentina Fil: Passalia, Mauro Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; ...